2017
DOI: 10.1371/journal.pone.0178050
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a novel mushroom from mycophagy community with emphasis on biomedical potency

Abstract: Mushrooms have been prized by humankind as medicine and culinary wonder since antiquity. Though several species are ethnically valued; many prospective species are still being discovered. One such wild macrofungus has recently been discovered during subsequent field surveys in West Bengal, India which in turn exposed as a traditionally consumed popular myco-food. The collected taxon was found to be unique with regard to its morphological as well as genetical features. After detailed characterizations, the fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…Firstly, chemical parameters of MLHWP were analysed spectroscopically which can be ranked in the following order: carbohydrates > protein (Table ). Carbohydrates, especially β‐glucan constituted the major proportion of this crude polysaccharide and its relative composition of is very much allied with previous published research findings on Russula alatoreticula , Macrocybe gigantea , Lentinus squarrosulus , Ganoderma applanatum and others.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Firstly, chemical parameters of MLHWP were analysed spectroscopically which can be ranked in the following order: carbohydrates > protein (Table ). Carbohydrates, especially β‐glucan constituted the major proportion of this crude polysaccharide and its relative composition of is very much allied with previous published research findings on Russula alatoreticula , Macrocybe gigantea , Lentinus squarrosulus , Ganoderma applanatum and others.…”
Section: Resultssupporting
confidence: 69%
“…When macrophages encounter foreign stimulus they become activated and undergo morphological changes along with cell enlargement. Several markers have been recognized as a positive sign of macrophage activation such as formation of vacuoles within the cytoplasm, lamellipodia generation and conversion of roundish cell shape to dendritic morphology . In the present study, to further confirm proliferation assay, morphological alterations of macrophages after polysaccharide treatment was determined.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Further, absolute predominance of β-glucan in Rusenan was detected as total glucan, β-glucan and α-glucan content were 15.63 ± 2.49, 12.11 ± 0.28, and 3.52 ± 2.51 g/100g dry polysaccharide, respectively. Comparative study with previous literature indicated that R. senecis might be consisted of more carbohydrate than that of R. alatoreticula (Khatua et al, 2017a), T. eurhizus (Chatterjee et al, 2013) and Schizophyllum commune (Klaus et al, 2011). Besides, the content of β-glucan as well as α-glucan were found to be in higher amount than that of Pleurotus florida (Saha et al, 2013) while the extent of protein was better than the hot water extract from Ganoderma lucidum and Agaricus bisporus (Kozarski et al, 2011).…”
Section: Resultsmentioning
confidence: 56%